EFEKTIVITAS LOW POWER LASER TERAPI DAN PROPRIOCEPTIF NEUROMUSCULAR FACILITATION PADA ULKUS DIABETIKUM DERAJAT 2 - Satria Nugraha, Made Hendra; Wahyuni, Nila; Sita Saraswati, Putu Ayu (Sport and Fitness Journal, 2019)
Diabetic ulcers are one of the most severe complications of diabetes in people with diabetes mellitus. When examined through the International Classification of Function (ICF) approach, there are several problems associated with diabetic ulcers, including: the presence of pain, limited movement, open wounds, loss of sensory sensation or motor ability. There are some modalities can be used to help these problems, namely by using laser and therapeutic approaches such as the application of proprioceptive neuromuscular facilitation (PNF). The method of this paper is an article review by using secondary data taken from research journals which are related to the effectiveness of the use of low power laser therapy and proprioceptive neuromuscular facilitation in diabetic ulcer patients. The primary effect of laser usage on cell is increasing oxidative metabolism to produce more ATP, which ultimately leads to the normalization of cell function, pain relief, and wound healing. PNF is a method of enhancing neuromuscular movement and facilitation to facilitate muscle contraction. This method has the primary goal of achieving individual needs, and thus can perform functional movements, through facilitation, inhibition, strengthening and relaxation of muscle groups. Based on the literature review, it can be concluded that: (1) Low power laser therapy is effective in repairing wounds in patients with grade 2 diabetic ulcers, (2) Proprioceptive Neuromuscular Facilitation (PNF) is effective in improving sensory and motor neuronal conduction associated with ankle movement in grade 2 diabetic ulcers, and (3) The combination of low power laser therapy and Proprioceptive Neuromuscular Facilitation is effective in improving the limitations of motion and function of grade 2 diabetic ulcers.